Trends in the development of the retail market in the context of digitalization - M. A. Samokhin (Путеводитель предпринимателя, 2025)
The article analyzes the retail market, taking into account the fact that digital tools and tools that help improve the efficiency of their activities are relevant at the current stage of economic development. Traditional approaches to product promotion, customer search, and expanding the geography of sales have become ineffective, as society is on the path to a new era of informatization and the availability of all kinds of online resources. Now not only large retailers, but also small businesses are actively switching to modern digital tools. The subject of the study is offline retailers offering online trading services.The research methodology includes a theoretical overview from the point of view of the author’s scientific approaches to understanding the essence of digitalization and its specifics in retail trade, as well as using the analysis method to study the dynamics of the retail market in current conditions, the comparison method allows you to evaluate and compare the main indicators in this area. Using the generalization method, conclusions are drawn and the results of the study regarding further trends are described. The results of the study contain generalizing conclusions regarding trends in the further development of digitalization and the introduction of innovative tools in the retail sector. The main trend highlights the need to develop new business strategies and approaches necessary for effective adaptation, flexibility and increased competitiveness of the modern trading market.